2020
DOI: 10.1007/s42804-020-00076-4
|View full text |Cite
|
Sign up to set email alerts
|

Paediatric endoscopic pilonidal sinus treatment: it is time to forget the open procedure?

Abstract: Purpose Our aim was to study the learning curve results with Paediatric Endoscopic Pilonidal Sinus Treatment (PEPSiT). Methods A retrospective observational study was performed in paediatric patients (< 18 year) with PEPSiT procedure. Complications, length of hospital stay and recurrence rate were analysed. Result In 2019, during the study period, 12 PEPSiT procedures were done. One patient was excluded from the study, because of the loss of follow-ups and two of them because of the use of the cystoscope. Intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 9 publications
(12 reference statements)
0
7
0
Order By: Relevance
“…Sixty studies were initially retrieved. Screening of these studies (abstract or full text when necessary) led to the exclusion of 51 studies, resulting in 9 studies [12][13][14][15][16][17][18][19][20] eligible for inclusion in this systematic review (►Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Sixty studies were initially retrieved. Screening of these studies (abstract or full text when necessary) led to the exclusion of 51 studies, resulting in 9 studies [12][13][14][15][16][17][18][19][20] eligible for inclusion in this systematic review (►Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…12,17 Of note, formal training or expertise of the performing surgeon/s on EPSiT is reported in four of the included studies, 12,13,15,18 while previous formal training or expertise is not specified in the remaining five studies. 14,16,17,19,20 Perioperative hair removal strategies varied significantly between and within studies (►Table 1). Routine preoperative and postoperative laser epilation was employed in two of the included studies 16,18 ; patients were instructed on regular hair removal postoperatively with shaving, depilatory creams, pulse light, or laser technology in six studies [13][14][15]17,19,20 ; in one study, hair removal strategies were not reported in perioperative wound care.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations